IMPACT OF DIGITAL ADVERTISING SEMIOTICS ON COSMETICS PRODUCTS IN AP REGION INDIA - Babu, T. Yogesh; Adinarayana, P. John; Babu, B. Kishore (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study of effect of digital advertising semiotics on cosmetics investigates how virtual advertising creativity has revolutionized Indian cosmetics enterprise in a good sized manner. The industry of cosmetics in India has matured sufficient where consumers are doing vast studies online earlier than honestly making their very last buy. The customers within the marketplace are looking for diverse merchandise, modern-day tendencies & dealers on-line, which make digital advertising more lucrative for the Indian skin care enterprise. The brand new trends have shown that it is mandatory for each Indian skincare organization to have a web presence through virtual advertising conversation blend.